Modification of cell volume and proliferative capacity of Pseudokirchneriella subcapitata cells exposed to heavy metal stress - Machado, Manuela D. (2014)
The impact of metals (Cd, Cr, Cu and Zn) on growth, cell volume and cell division of the freshwater alga Pseudokirchneriella subcapitata exposed over a period of 72 h was investigated. The algal cells were exposed to three nominal concentrations of each metal: low (closed to 72 h-EC10 values), intermediate (closed to 72 h-EC50 values) and high (upper than 72 h-EC90 values). The exposure to low metal concentrations resulted in a decrease of cell volume. On the contrary, for the highest metal concentrations an increase of cell volume was observed; this effect was particularly notorious for Cd and less pronounced for Zn. Two behaviours were found when algal cells were exposed to intermediate concentrations of metals: Cu(II) and Cr(VI) induced a reduction of cell volume, while Cd(II) and Zn(II) provoked an opposite effect. The simultaneous nucleus staining and cell image analysis, allowed distinguishing three phases in P. subcapitata cell cycle: growth of mother cell; cell division, which includes two divisions of the nucleus; and, release of four autospores. The exposure of P. subcapitata cells to the highest metal concentrations resulted in the arrest of cell growth before the first nucleus division [for Cr(VI) and Cu(II)] or after the second nucleus division but before the cytokinesis (release of autospores) when exposed to Cd(II). The different impact of metals on algal cell volume and cell-cycle progression, suggests that different toxicity mechanisms underlie the action of different metals studied. The simultaneous nucleus staining and cell image analysis, used in the present work, can be a useful tool in the analysis of the toxicity of the pollutants, in P. subcapitata, and help in the elucidation of their different modes of action.